Effectiveness of EMR Training To Readiness Of Professional Health Workers To Use EMR In Health Services : Meta Analysis - Hendra Dwi Kurniawan; Rizki Aqsyari. D; Aem Ismail; Julhan Irfandi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Health services are undergoing changes in terms of digitalization. Electronic Medical Record (EMR) is one form of change in the impact of digitalization in the health service sector. It is hoped that the existence of EMR in the health services sector can improve the performance of health workers in providing services to patients so that it can improve the level of public health. However, with EMR there are still problems in its use. Many health service institutions apply several methods to adapt to changes or novelties in the field of EMR, one of which is by providing training on the use of EMR to health workers. This research aims to determine the effectiveness of EMR training on the readiness of health workers in using EMR in health services. This research uses meta analysis and systematic review methods with the PICO model (P = EMR users, I = EMR training, C = Non EMR training, O = readiness to use EMR). Articles were obtained through searching articles in the PubMed database. The articles used are full-text articles from 2019 to 2024. Articles were selected using the PRISMA flow diagram. Articles were analyzed using the RevMan 5.3 application. A total of 5 articles analyzed came from Ethiopia. The study results show that EMR training can increase the readiness of health workers to use EMR to support health services (aOR = 1.87; CI 95% = 0.92 – 3.79; p = 0.08). Health workers who receive EMR training will be 1.87 times better prepared to use EMR in health services than health workers who do not receive previous EMR training.